School Fairness and Repeated Bullying Victimization Among High School Students - Overstreet, Suzanne (Crime & delinquency, 2023)
Recent research has shown a link between fairness in terms of school rules and discipline and negative student outcomes, including delinquency, violent behavior, and victimization. The current study examines how fairness at school impacts bullying victimization—operationalized as repeated physical, psychological, or verbal victimization—among high school sophomores. We tested this hypothesis using one wave of the Educational Longitudinal Study (2002). The findings of negative binomial regression analyses indicate bullying victimization is more prevalent among students who believe that their schools are unfair. A number of student characteristics were also significantly related to experiencing bullying. Implications for policy and practice are outlined.